Ranma 1/2. Vol. 5 - Takahashi, Rumiko, 1957- (Viz graphic novel., 2003)
Due to some strange training by his father, Ranma can't stand cats. Exposed to a cat for too long, he turns into one--and becomes invincible! Meanwhile, Shampoo returns with her great-grandmother, the "honorable hag, " who magically makes Ranma unable to tolerate hot water. Shampoo has also been to the magical springs, and now turns into a cat! When Shampoo's ardent suitor Mousse arrives, female Ranma has no choice but to try to defeat him